2018
DOI: 10.3168/jds.2017-13032
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of colostrum replacer versus maternal colostrum on immunological status, health, and growth of preweaned dairy calves

Abstract: Commercially available colostrum replacers (CR) are commonly used when maternal colostrum (MC) is unavailable, for managerial convenience, to ensure quality consistency at first feeding, or in disease control and eradication programs. The objective of this study was to determine the efficacy of feeding First Day Formula (Accelerated Genetics, Baraboo, WI) CR versus pooled MC on immunological status, growth, and health of preweaned dairy calves. A total of 1,220 Jersey and Jersey × Holstein calves born on a Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 29 publications
(51 reference statements)
4
42
1
17
Order By: Relevance
“…Evidence indicates a beneficial rearing result with feeding of colostrum with a high antibody concentration (84 mg/mL), 2 litres in the first feeding and 2 litres at 12 hour of life, compared with feeding 4 litres of colostrum after birth (Jaster, 2005). This confirms the theory that in the first feeding the calf should acquire about 150-200 g of IgG (Lago et al, 2018).…”
Section: Introductionsupporting
confidence: 63%
“…Evidence indicates a beneficial rearing result with feeding of colostrum with a high antibody concentration (84 mg/mL), 2 litres in the first feeding and 2 litres at 12 hour of life, compared with feeding 4 litres of colostrum after birth (Jaster, 2005). This confirms the theory that in the first feeding the calf should acquire about 150-200 g of IgG (Lago et al, 2018).…”
Section: Introductionsupporting
confidence: 63%
“…Although not true of all products, studies have shown that several commercially available CR products, when administered at a high enough IgG mass (150-200 g of IgG) within a few hours after birth, can provide acceptable serum IgG concentrations when using a conventional goal for APT (eg, 90% of calves with serum IgG 10 g/L). [119][120][121][122] However, if producers hope to achieve the more ambitious goals for passive transfer that are proposed in relation to monitoring, the authors suggest that they may need to deliver at least 300 g of IgG in a CR product. Research is required to investigate this hypothesis.…”
Section: Use Of Colostrum Supplements or Replacement Productsmentioning
confidence: 99%
“…When colostrum quality is poor or unavailable, colostrum replacers (CRs) may be an alternative. Lago et al [62] reported that CR-fed calves had a lesser probability of receiving contaminated liquid feed and performed similar in terms of health compared with calves receiving high-quality colostrum. Therefore, CRs can be an alternative to poor-quality colostrum.…”
Section: Factors Shaping the Quality And Chemical Composition Of Colomentioning
confidence: 99%